P138 An innovative approach to study design: using electronic medical records to inform the feasibility and design of the novelty study (a novel observational longitudinal study on patients with asthma and/or COPD). (15th November 2016) - Reddel, HK; Gerhardsson de Verdier, M; Agustí, A; Beasley, R; Bel, EH; Janson, C; Make, B; Martin, RJ; Pavord, I; Postma, D; Price, D; Keen, C; et al.
Abstract : Introduction: Asthma and COPD have traditionally been viewed as distinct diseases. While they have overlapping biological mechanisms, past studies often focused on specific aspects of each disease based on a single diagnostic label, and many clinical trial populations were defined by strict enrolment criteria with limited generalisability. NOVELTY is a prospective, multinational, observational, longitudinal cohort study aiming to enrol 14, 800 patients aged ≥12 years with a diagnosis or suspected diagnosis of asthma and/or COPD. In this population, the objectives of NOVELTY are to: (i) describe patient characteristics, treatment patterns and burden of illness over time in clinical practice; and (ii) use biomarkers and clinical parameters to identify phenotypes and endotypes associated with differential outcomes for symptom burden, clinical evolution and healthcare utilisation. Aim: This feasibility analysis of electronic medical records (EMRs) aimed to understand the potential study population, assess patient numbers across disease severities and evaluate EMRs as a data source for NOVELTY. Methods: EMRs from patients with asthma and/or COPD were identified from national databases covering primary and specialist care in 11 countries (Table). Disease severity was classified using treatment- and/or lung function-based algorithms for asthma and COPD. EMR variable coverage and completeness were assessed for standardised clinical, laboratory and physiological data and patient-reported outcomes (PROs). Results: EMRs for 921, 888 patients with asthma, 958, 945 with COPD and 117, 893 with both diagnoses were identified. EMRs routinely documented patient demographics and characteristics, but many disease- and treatment-related data, and PROs/symptoms required for evaluation of disease severity and clinical outcomes were frequently missing (not collected or not documented; Table). Disease severity could not be classified in 561, 837 patients (asthma) and 355, 743 patients (COPD), representing 22−100% and 7−85% of patients across countries. Conclusions: EMR analysis revealed numbers of patients per country potentially eligible for NOVELTY. Many variables required to meet NOVELTY objectives were missing in EMRs (e.g. lung function and PRO/symptoms); therefore, variables in NOVELTY will primarily be documented in electronic case report forms, not EMRs. The lack of lung function data in many countries suggested divergences in diagnosis of asthma/COPD between clinical guidelines (which include lung function tests) and clinical practice.